ANALISA WAKTU TERHADAP BIAYA AKIBAT PENAMBAHAN JAM KERJA PADA PROYEK PEMBANGUNAN GEDUNG GEREJA KATEDRAL KOTA SAMARINDA - SETIAWAN, HERU (KURVA S JURNAL MAHASISWA, 2018)
In the development of construction activities, losing something that happens very often in the field. Acceleration is needed to drill or minimize the jam. The acceleration efforts carried out certainly affect the increase in project costs. An analysis of the time and additional costs per acceleration is needed. There are many ways that can be done, one of which is to increase working hours overtime. With this number of working hours, you will get the right amount of this amount to find out the optimum time and amount of costs. Case studies were carried out at the Construction of the Samarinda Church Building with a total project cost of Rp. 7,991,295,673.00 with project projection time of 28 weeks or 168 working days. The alternative acceleration made at this time is to analyze working hours for 2 hours, 3 hours and 4 hours. Furthermore, an analysis of Microsoft Project 2016 was carried out which resulted in a path that would be an activity to be optimized and to analyze the relationship between time and costs that occurred after the Crashing Program. Maximum acceleration occurs during working hours for 4 hours which is 149 working days or 19 days faster than normal duration, while acceleration costs occur during working hours for 1 hour with an additional fee of Rp. 18,076,663.00 or the total increase of 0.226% of the total project costs.